Exemplary and Habituation of Parents' Religious Behavior for Early Childhood Moral and Religious Development - Antoni, Apri (CV. Creative Tugu Pena, 2025)
This study aims to examine the role of exemplary and habituation of parents' religious behavior in supporting the moral and religious development of early childhood. Children in the early age stage are in the phase of imitation and value formation, so the family environment, especially parents, is the main factor in instilling moral and religious values. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation on families in the Tulangbawang Lampung. The results showed that parents' exemplary religious practices such as worshipping, praying, and telling the truth consistently have a positive influence on children's behavior. In addition, the habituation of religious activities in daily routines, such as reading prayers together and attending family religious activities, strengthens children's understanding of moral and spiritual values. Thus, exemplification and habituation carried out consistently by parents prove to be an important foundation in shaping children's religious character from an early age.